Is portable three-dimensional ultrasound a valid technique for measurement of postpartum urinary bladder volume? - Nusee, Zalina; Ibrahim , Norliza; Mohd Rus, Razman; Ismail, Hamizah (Elsevier, 2014)
A total of 190 paired measurements were performed on 190 women aged between 16 and 47 years. Majority of the women (36.9%) were in their first parity (range: 1-9). The mean BV was 159.46 mL [standard deviation (SD) ¼ 99.78; range: 17e593 mL] on three-dimensional (3D) UBS and 143.76 mL (SD ¼ 104.89; range: 2-588 mL) on catheterization. The mean difference between the two values was 15.70 mL (SD ¼ 69.31, p < 0.001). The Foley’s catheter was clamped for a minimum of 30 minutes and a maximum of 260 minutes. The UBS measurements were highly correlated with the BV obtained by catheterization (r ¼ 0.819; p < 0.001). There was no significant difference between UBS and catheterized volume in a different volume subgroup. There were 35 cases (18.2%) with the difference in measurement of more than 25%. Twenty-five cases were associated with a catheterized volume less than 50 mL. There were a total of 33 cases with true BV of less than 50 mL, and only eight cases (24.24%) had an accurate measurement. The UBS tends to overestimate BV between 2 and 270 mL in this group. There was a significant linear relationship between the difference in measurement and body weight and duration of clamping. Conclusion: Measurement of BV in immediate postpartum period using UBS is comparable with urethral catheterization. The accuracy of measurement is affected by body weight and increasing amount of BV.